A deep learning-based method for improving the efficiency of integrating multimedia teaching resources in Civics and Political Science courses in universities, middle schools and elementary school - Wang, Tianzuo (Applied mathematics and nonlinear sciences, 2025)
This paper designs a deep learning-based multimedia teaching resources sharing platform for Civics and Political Science courses in primary and secondary schools to improve the efficiency of multimedia teaching resources integration. Using Python language to design a web crawler program to obtain the multimedia teaching resources data of Civics and Political Science in primary and secondary schools in the webpage, and using K-means algorithm to classify and integrate the obtained resource data. Based on deep learning technology, we designed a multimedia teaching resources sharing platform for Civics and Political Science courses in primary and secondary schools, and tested its application. The K-means clustering algorithm used in this paper has a faster convergence speed of clustering, and the time spent on completing the clustering of five kinds of samples is 64 s. The teaching resource sharing platform has good performance compared to other methods in the stress test and transmission delay test. Teaching resources can be utilized at a rate of up to 99.93%, which is 13.69% and 31.40% higher than traditional teaching resource sharing methods and IoT-based teaching resource sharing methods, respectively. In this paper, the application of multimedia teaching resource sharing platform for Civics and Political Science classes in universities and elementary school will significantly improve the efficiency of Civics and Political Science integration in universities and elementary school, and accelerate the integration of multimedia teaching resources for Civics and Political Science classes in universities and elementary school.